2017
DOI: 10.1371/journal.pone.0183324
|View full text |Cite
|
Sign up to set email alerts
|

The Helicobacter pylori type IV secretion system promotes IL-8 synthesis in a model of pediatric airway epithelium via p38 MAP kinase

Abstract: Epidemiologic studies have reported an inverse relationship between childhood Helicobacter pylori infection and development of allergic asthma. Because lung epithelium plays an important role in allergic asthma pathogenesis, we hypothesized that H. pylori may directly influence airway epithelial cell innate immune function, particularly in early childhood. To test our hypothesis, we established an in vitro H. pylori infection model using primary tracheobronchial epithelial cell cultures derived from infant, ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Despite various studies have identified the potential protection from the gastrointestinal H. pylori on the allergy of asthma 27 , the research on the immunomodulation of airway epithelium is limited. Colonized H. pylori may participate in the pathogenesis of young asthma by inducing the activation of MAPK p38 protein and the increased production of IL-8, which is tightly associated with the recruitment of neutrophil 28 , 29 . But H. pylori may play a different role in adults' asthma, especially in the different inflammatory phenotypes and needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Despite various studies have identified the potential protection from the gastrointestinal H. pylori on the allergy of asthma 27 , the research on the immunomodulation of airway epithelium is limited. Colonized H. pylori may participate in the pathogenesis of young asthma by inducing the activation of MAPK p38 protein and the increased production of IL-8, which is tightly associated with the recruitment of neutrophil 28 , 29 . But H. pylori may play a different role in adults' asthma, especially in the different inflammatory phenotypes and needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Although only H.pylori is associated with the activation of E-cadherin/β-catenin/TCF-4 signaling pathway in normal gastric epithelial cells (Yu et al, 2011 , 2014 ), both pathogens are linked to the activation of NF-κβ and MAP kinases oncogenic pathways in GC cell lines (Mohr et al, 2014 ; Liu and Cohen, 2015 ; Byun et al, 2016 ; Dela Pena-Ponce et al, 2017 ). Co-infection by EBV can also hinder the host response to H. pylori .…”
Section: Infectious Agents In Gastric Cancermentioning
confidence: 99%
“…Dela Pena‐Ponce et al studied the effect of H. pylori and CagA‐positive strains in a model of pediatric airway epithelium, focusing on the activation of inflammation. Results showed that H. pylori preferentially elicited IL‐8 production via p38 MAP kinase, thus theoretically exhibiting a protective effect in allergic asthma . Similarly, in an animal study, van Wijck et al demonstrated that the administration of an H. pylori extract prior to the allergen challenge on C57BL/6 mice reduced the processing of allergen by dendritic cells in the lungs and mediastinal lymph nodes .…”
Section: Respiratory Diseasesmentioning
confidence: 97%